IMPLEMENTASI PROGRAM FASILITAS PEMBIAYAAN PEROLEHAN RUMAH HUNIAN TERJANGKAU MILIK BAGI MASYARAKAT BERPENGHASILAN RENDAH DI PROVINSI DKI JAKARTA - Nisrina Mahfudhoh; Sri Suwitri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The Affordable Housing Financing Facility Program is a policy of the Jakarta Provincial Government to expand access to home ownership for Low-Income Communities (MBR). However, despite policy changes such as adjustments to administrative requirements and maximum income limits, the number of beneficiaries has actually decreased. This study aims to answer questions about how the program is being implemented and the factors hindering its implementation. The results indicate that the program's implementation adheres to the provisions of Jakarta Governor Regulation Number 14 of 2020, with a financing scheme with no down payment and fixed interest rates, involving local governments, banks, and developers. However, program implementation has not been optimal due to persistent barriers in communication, resources, disposition, and bureaucratic structure. These barriers include uneven information delivery, suboptimal use of digital media, banking prudence in risk assessments, delays in handling complaints, and fragmented authority that slows down financing disbursement and the resolution of problem loans. Based on these findings, this study recommends updating cooperation agreements with banks, reviewing the Environmental Management Fee (IPL) amount, and strengthening inter-agency evaluation and coordination to make the program more effective and sustainable.